Development of B cells in the gut-associated lymphoid tissue of mid-gestational fetal lambs - Alitheen, Noorjahan; McClure, Susan; McCullagh, Peter (Elsevier, 2003)
Intestinal mucosal immune system development was investigated in fetal lambs from 61 to 110 days (term, 150 days). Fetal small intestine was examined at 400 mm intervals for the presence of IgM+ cells. The first phase of B cell development was characterised by increase in B cell density throughout the jejunum from 65 days. Increase in density was greatest in the proximal jejunum and declined progressively approaching the ileum. The second phase entailed a decrease in jejunal B cell concentration, evident from 90 days. The average number of cells per field diminished, by 110 days, to a 10th that at 90 days. Failure of B cell increase to match a five-fold intestinal lengthening may have contributed to this. Overlapping the two phases of jejunal B cell development was a third phase of major expansion of B cell density in the terminal ileum.